Status of Asterina exsiccatae in Herbarium Cryptogamae Indiae Orientalis (HCIO), New Delhi, India - HOSAGOUDAR, V.B.; MAHESWARI, UMA; AGARWAL, D.K. (Indian Phytopathology, 2011)
Herbarium Cryptogamae Indiae Orientialis was founded by E.J. Butler in the year 1901 for the deposition of infected plant materials in Pusa and is now in the Division of Plant Pathology, Indian Agricultural Research Institute, Pusa Campus, New Delhi. This herbarium is of international recognition and housed more than 48,000 fungal specimens belonging to different groups of fungi. Of these, genus Asterina infected materials (486 exsiccatae belonging to 181 taxa on 271 host plants) is dealt herewith. All the fungal species are arranged alphabetically